(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The technique of adsorption is one of the most important processes which are widely used in the treatment of water and wastewater. The technique of adsorption which is a very effective and efficient method in the treatment of pollutants. One of the disadvantages of the process of adsorption using activated carbon is expensive, and this has made researchers think of finding cheap alternatives to reduce the cost this process. In the present study, activated carbon was prepared from the cactus plant for the purpose of its use to remove Ni+2 ions. Batch tests were conducted to evaluate the ability of Cactuses plant in the removing of Ni+2 ions from wastewater. The results showed that activated carbon developed from Cactuses has good ability to remove Ni+2 ions. It was found that the maximum removal efficiency reached to a value of 99.68 % under pH equals to 6.